Public Presentation of Two Extended Essays by Yuji Zhang - Phan, Vu Thuy Anh (Stream: Interdisciplinary Journal of Communication, 2015)
Our dear colleague, Yuji Zhang, will defend her two MA extended essays on Thursday, January 14th, 2016 at Harbour Centre, Room HC 1415 (2:30-4:30). Here are the abstracts of the two extended essays: “China’s Quest for Soft Power” and "Re-examining Herbert Schiller’s Cultural Imperialism Thesis"